Combinations of chronic conditions, functional limitations and geriatric syndromes associated with periodontal disease. Issue 3 (23rd August 2022) - Alqahtani, Hussam M; Koroukian, Siran M; Stange, Kurt; Bissada, Nabil F; Schiltz, Nicholas K
Abstract : Objective: To identify complex multimorbid conditions, including chronic conditions, functional limitations and geriatric syndromes, associated with the presence and severity of periodontal disease (PD), after accounting for a series of demographic and behavioural characteristics. Design: This cross-sectional study used secondary data from a nationally representative sample, classification and regression tree analysis and random forest identified combinations of specific conditions constituting complex multimorbidity associated with the presence and severity of PD. Setting: US National Health and Nutritional Examination Survey (2013–2014). Participants: Individuals 60 years of age or older who completed a periodontal examination. Results: Among 937 participants aged 60 and over, the prevalence of PD was 72.6%. PD was associated with sociodemographic factors and limitations in instrumental activities of daily living. Male sex and non-white race were the two most critical predictors of stage III/IV PD. Other important factors included age, education level and the federal poverty level. Conclusions: Rather than chronic conditions or geriatric syndromes, PD was associated with sociodemographic factors and functional limitations. Accounting for the co-occurrence of sociodemographic and functional limitations will help recognise older adults who are at an increased vulnerability to the severity of PD.